Highway Infrastructure and the Economy Implications for Federal Policy - Shatz, Howard J. (RAND Corporation, 2011)
To inform debate on a new transportation bill being considered, the authors review the literature on the economic outcomes of highway infrastructure spending, which constitutes the largest share of federal spending on transportation infrastructure. They highlight the connections between highway spending and the economy and then analyze the literature to trace the effects of highway infrastructure on productivity, output, and employment.